Relative age effect in Italian soccer: a cultural issue in talent management? - Ruscello, B.; Morganti, G.; Apollaro, G.; Saponara, A.; Esposito, M.; Marcelli, L.; Filetti, C.; Porta, M.; Grossi, A.; Pantanella, L. (The Journal of Sports Medicine and Physical Fitness, 2023)
BACKGROUND: Relative age effect (RAE) is a well-known phenomenon among those involved in youth sports, especially when the sport being investigated is widespread and involves early selection for participation in national and international competitions. METHODS: The purpose of this study was to verify whether the Italian youth soccer ecosystem has adapted to this issue over the years, comparing players born in 1995 and in 2005 and been playing in Under 16 teams in the appropriate years. The sample included 13 professional Italian soccer teams. The number of players analysed was 260 (1995) and 344 boys (2005), respectively, making a total of 604 players enrolled in this study. RESULTS: Relative age effects were detected by x2 goodness of fit tests both in players born in 1995 (P<0.000;V=0.40) and in 2005 (P<0.0001;V=0.39). Chi² test of independence showed no significant difference between the two groups of players (P=0.986;V=0.02), confirming a substantial parity of the phenomenon over the two investigated birth years. CONCLUSIONS: Ten years of research and dissemination of RAE did not change the selection policies adopted by coaches and/or scouts, who favor relatively older players during the selection processes. Therefore, RAE appears as the result of the Talent Identification and Development Structures, characterized by early selection and early specialization, and which consider performance as the pre-requisite for gaining access to the next developmental stages. Sport organizations should be aware of this issue and counteract accordingly, since it is important to mitigate the presence of RAE, as it causes inequality of opportunity.